(untitled) (The Research of Medical Science Review, 2025)
Background: Polycystic ovary syndrome (PCOS) is a serious clinical issue of the present age. It mostly affects women of reproductive age. Obesity is considered a potential risk factor associated with PCOS. This systematic review was conducted to evaluate the prevalence of polycystic ovary syndrome (PCOS) in relation to body mass index (BMI) variations across different populations. Methodology: A comprehensive search was performed using Google Scholar, Springer, and PubMed to identify relevant articles. The search was limited to studies published within the last 20 years (2005 - 2025). Only Studies reporting mean BMI, mean age, and prevalence of PCOS in the study population were chosen, while others were excluded. Result: Through database searching with pertinent keywords, such as Google Scholar (n = 80), PubMed (n = 10), and Springer (n = 10), a total of 100 entries were found. Fifty of the 85 records that were left after duplicates were eliminated were screened. After the screening procedure, 35 full-text papers were evaluated for eligibility; 20 studies were disqualified in accordance with the inclusion criteria. In the end, the comprehensive systematic review had 15 studies. Conclusion: BMI plays a crucial role in PCOS development and severity, increasing risks of metabolic and hormonal complications, emphasizing the need for standardized diagnosis and personalized treatment